Diseño e implementación de un sistema Scada para el proceso overhead de sellado en OMNIBUS BB - Betancourt Reyes, Diego Paúl (2012)
The sealing process overhead consists of 12 vehicles comprised of 2 electrical hoists and a drive motor for transport, this vehicle carries chassis through 5 work stations where chassis is sanded from anticorrosive paint, joints are sealed and chassis is protected against abrasion. The SCADA system provides monitoring of real time processing, presentation of failure reports that contains a description, duration and date of register, and processing stops activated by the operator, giving valuable information to the departments of maintenance and production in order to minimize process downtime. The SCADA system also consists of a maintenance plan that provides information to do a general overhaul of the entire equipment.